Temporal Proteomics of Inducible RNAi Lines of Clp Protease Subunits Identifies Putative Protease Substrates. Issue 2 (11th December 2017) - Moreno, Juan C.; Martínez-Jaime, Silvia; Schwartzmann, Joram; Karcher, Daniel; Tillich, Michael; Graf, Alexander; Bock, Ralph
Abstract : Generation of inducible knockdown mutants for components of the plastid Clp protease system and time-resolved analysis of changes in their proteome allows the identification of a set of putative protease substrates. Abstract: The Clp protease in the chloroplasts of plant cells is a large complex composed of at least 13 nucleus-encoded subunits and one plastid-encoded subunit, which are arranged in several ring-like structures. The proteolytic P-ring and the structurally similar R-ring form the core complex that contains the proteolytic chamber. Chaperones of the HSP100 family help with substrate unfolding, and additional accessory proteins are believed to assist with Clp complex assembly and/or to promote complex stability. Although the structure and function of the Clp protease have been studied in great detail in both bacteria and chloroplasts, the identification of bona fide protease substrates has been very challenging. Knockout mutants of genes for protease subunits are of limited value, due to their often pleiotropic phenotypes and the difficulties with distinguishing primary effects (i.e. overaccumulation of proteins that represent genuine protease substrates) from secondary effects (proteins overaccumulating for other reasons). Here, we have developed a new strategy for the identification of candidate substrates of plant proteases. By combining ethanol-inducible knockdown of protease subunits with time-resolved analysis of changes in the proteome, proteins that respond immediately to reduced protease activity can be identified. In this way, secondary effects are minimized and putative protease substrates can be identified. We have applied this strategy to the Clp protease complex of tobacco ( Nicotiana tabacum ) and identified a set of chloroplast proteins that are likely degraded by Clp. These include several metabolic enzymes but also a small number of proteins involved in photosynthesis.